Blockchain and Artificial Intelligence Technologies for Balanced Foreign Trade: Replacing Exchange Function of Money - Mustafa Emre Civelek; Oksan Kibritci Artar (European Scientific Journal, ESJ, 2019)
Today, the capitalist economy has entered into a dead end. Unemployment is expected to reach an unprecedented level due to the rise of automation and artificial intelligence technologies. The creation of excess fiat money will not be a remedy for the collapse of the capitalist economy. In the future, a new economic model open to government intervention will be needed. Moreover, if global monetary system collapses, government should find a solution to continue foreign trade in order to meet the needs of their citizens. Trade unions are classical means that increase trade among the member countries, but they cause imbalance in mutual trade volumes. The advent of blockchain and artificial intelligence technologies will bring an end to the obsolete and outdated foreign trade methods. These technologies will also lead to the emergence of balanced trade unions across countries. This paper focuses on defining a new system known as intelligent trade matrix, suggesting that this system will allow barter transactions between two countries without imposing any customs duty.